The Role of the National Qualifications Framework in the Jordan Education System - Zaid Ahmed Al-Anber; Thafer Y. Assaraira; Saad Bani-Mohammad; Zeid A. Albashaireh (International Journal of Advanced Science and Computer Applications, 2023)
Jordan is part of the structuring of the international Qualification Framework. The Jordan qualification framework, JNQF, is a national strategy for managing and regulating all national qualifications in the education and training sectors in a single comprehensive qualification framework. The JNQF consists of 10 levels for both academic and vocational pathways. The descriptors of JNQF which are designed in terms of learning outcomes, help to map the vertical level of complexity of a particular qualification and help to clarify its horizontal orientation, be this knowledge, skills, or competences. The main advantages of JNQF are: enhancing the image of vocational education and training (VET), bridging the academic and vocational pathways, facilitating lifelong learning, shifting the paradigm from input-oriented learning/training into leaning outcomes-based, recognizing individual learning pathways and opening up the possibilities to bring closer education/training providers in the labor market.